The Relationship Among Perceptual Similarity, Sex, and Performance Ratings in Manager-Subordinate Dyads - Pulakos, Elaine D.; Wexley, Kenneth N. (Academy of Management Journal, 1983)
The relationship of perceptual similarity and sex in both manager and subordinate performance appraisals within manager-subordinate dyads was investigated. Perceptual similarity accounted for a sizable percentage of performance rating variance. Significantly lower performance appraisals were found in dyads in which there was mutual perceptual dissimilarity between managers and subordinates.